Possibilities and prospects for glucocorticoid withdrawal in systemic lupus erythematosus - S. K. Solovyev; E. A. Aseeva; E. L. Nasonov; A. M. Lila; G. M. Koilubaeva (Современная ревматология)
The efficiency of glucocorticoid (GC) therapy for systemic lupus erythematosus (SLE) is beyond question and is confirmed by the experience gained over many decades of their use. However, there are many problems with prolonged GC use, even in its low and medium doses. In particular, the development of GC-associated irreversible organ damages significantly worsens prognosis and causes a decrease in quality of life and social adaptation and a substantial increase in treatment costs. On the other hand, the current capabilities of early diagnosis, pathogenetic therapy, and monitoring in many patients with SLE allow for maintaining low disease activity and remission, the conditions in which the feasibility of further GC treatment can and should be decided. The paper gives the data available in the literature and the authors’ own studies on the possibility and prospects of GC withdrawal in SLE patients in a stage of low disease activity and remission.